Microsatellite and Mitochondrial COI Provide Novel Insights Into the Population Genetic Structure of White Prunicola Scale (Pseudaulacaspis prunicola) in China - Minmin Niu; Dengen Fu; Haoyang Wang; Yun Liu; Xuanxing Du; Qing Zhao; Jiufeng Wei (Ecology and Evolution)
ABSTRACT The white prunicola scale Pseudaulacaspis prunicola (Maskell) is an important pest of fruit and ornamental plants, characterised by its wide distribution, broad host range and distinct biological traits. In this study, a comprehensive population genetic analysis of P. prunicola in China was conducted, focusing on genetic diversity, genetic structure, relationships among geographical populations, and population dynamics. Microsatellite molecular and mitochondrial COI markers were used to examine the genetic diversity and structure of 19 P. prunicola populations across 10 provinces in China. The results revealed low genetic diversity and limited gene flow among populations. A clear geographic genetic structure was identified, with the 19 populations being, divided into four distinct groups, showing a pronounced north–south distribution pattern. Significant genetic differentiation was observed between these groups, with minimal gene exchange. COI‐based diversity analyses produced results similar to those obtained from the microsatellite markers. These findings provide valuable insights into the distribution and spread of P. prunicola in China and may help inform the development of effective and targeted pest control strategies.